NetLangEd, a web editor to support online comment annotation - Rodrigues, Rui (2021)
This paper focuses on the scientific areas of Digital Humanities, Social Networks and Inappropriate Social Discourse. The main objective of this research project is the development of an editor that allows researchers in the human and social sciences or psychologists to add their reflections or ideas out coming from reading and analyzing posts and comments of an online corpus 1. In the present context, the editor is being integrated with the analysis tools available in the NetLang platform. NetLangEd, in addition to allowing the three basic operations of adding, editing and removing annotations, will also offer mechanisms to manage, organize, view and locate annotations, all of which will be performed in an easy, fast and user-friendly way.